Identifying Early Conception Using Ultrasound in Ovsynch Treated Postpartum Anestrus Gir Cows - Parikh, SS; Kavani, FS; Raval, RJ; Vala, KB; Makwana, RB (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The aim of this study was to detect early conception using transrectal ultrasonography in postpartum anestrus Gir cows treated with  Ovsynch protocol (Group-I, n=11), keeping the same number of normal cyclic cows as control (Group-II, n=11). Ultrasonography  examinations were performed using a real-time B-mode ultrasound scanner equipped with 7.5 MHz convex array transducer on day  11, 22 and 32 post-AI to monitor ovarian structures and uterine changes. Cent percent of anestrus animals responded to the Ovsynch  protocol with clear signs of estrus. The conception rates at induced and second estrus in the treatment group were 45.45 and 33.33%,  respectively, with an overall conception rate of 2 cycles post-treatment as 63.63%. In the control group, first service, second service  and overall conception rates of 2 cycles were 36.36, 14.28 and 45.45%, respectively. The results obtained were better with the Ovsynch  protocol. Ultrasound scanning on day 22 and 32 revealed visualization of the fluid and embryonic vesicle, respectively. Early embryonic  death occurred in one cow out of six between days 22 and 32 post-AI in ovsynch treated group.
Keywords: Gir cows; Anestrus; Ovsynch; Ultrasonography; Conception rate